2022
DOI: 10.3389/fimmu.2022.867707
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Respiratory Coronavirus as a Model for Acute Respiratory Coronavirus Disease

Abstract: In the light of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, we have developed a porcine respiratory coronavirus (PRCV) model for in depth mechanistic evaluation of the pathogenesis, virology and immune responses of this important family of viruses. Pigs are a large animal with similar physiology and immunology to humans and are a natural host for PRCV. Four PRCV strains were investigated and shown to induce different degrees of lung pathology. Importantly, although all four strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 87 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Porcine respiratory coronavirus causes a subclinical disease in pigs, which in some cases results in fever, sneezing or mild coughing, and combined with other pathogens such as porcine respiratory and reproductive syndrome (PRRS) and swine infl uenza virus (SIV) can be a part of a post-weaning porcine respiratory disease complex (PRDC) that causes a signifi cant economic loss in swine industry (Brockmeier et al, 2002). However, strains 135 and 137 of PRCV are capable of producing similar pulmonary lesions to that of the swine infl uenza virus (Keep et al, 2022). Furthermore, a co-infection of PRCV and PRRS induces a disease with severe respiratory signs (Jung et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine respiratory coronavirus causes a subclinical disease in pigs, which in some cases results in fever, sneezing or mild coughing, and combined with other pathogens such as porcine respiratory and reproductive syndrome (PRRS) and swine infl uenza virus (SIV) can be a part of a post-weaning porcine respiratory disease complex (PRDC) that causes a signifi cant economic loss in swine industry (Brockmeier et al, 2002). However, strains 135 and 137 of PRCV are capable of producing similar pulmonary lesions to that of the swine infl uenza virus (Keep et al, 2022). Furthermore, a co-infection of PRCV and PRRS induces a disease with severe respiratory signs (Jung et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Th e deletion in the S gene resulted in a change in the spike protein of PRCV, thus inhibiting binding to the sialic acid and entering enterocytes (Turlewicz-Podbielska and Pomorska-Mól, 2021). Th e PRCV replicates in the lungs and causes a subclinical to mild infection of the respiratory tract, but induces a strong immunological response to the infection raising the levels of interferons and interleukins (Turlewicz-Podbielska and Pomorska-Mól, 2021; Keep et al, 2022). Since TGEV and PRCV are closely antigenically related, the antibodies against PRCV cross-react with the TGEV antigen thus protecting pigs against TGEV infection (Whittaker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we used enveloped (SARS-CoV-2 and PRCV) and non-enveloped (CVB3) viruses to test the antiviral activity of our DBD plasma system. Both SARS-CoV-2 and PRCV are enveloped RNA viruses that belong to the Coronaviridae family and present morphological, biophysical, and genomic similarities, 32 which makes PRCV a suitable surrogate virus model for SARS-CoV-2. The parameters required for NTP inactivation of SARS-CoV-2 and the surrogate virus PRCV were similar, while longer treatment times were needed for the CVB3 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed severe pulmonary consolidation in TGEV-infected piglets for the frst time. Pulmonary consolidation had only reported in PRCV, a respiratory variant of TGEV, infected piglets [12].…”
Section: Discussionmentioning
confidence: 99%
“…Isabel Sola demonstrated that deletion of the ORF3 gene in TGEV has little efect on its virulence and replication [11]. Porcine respiratory coronavirus (PRCV), a respiratory variant of TGEV, difers from TGEV by approximately 600 nucleotides of deletion in the S gene and a partial deletion in the ORF3 region, which may afect the tissue tropism and clinical disease of PRCV [12,13]. Although the relationship between PRCV and TGEV is complex, it still reminds us that variations in the S gene and ORF3 have the potential to infuence the clinical symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%